Direct Delivery of ANA-TA9, a Peptide Capable of Aβ Hydrolysis, to the Brain by Intranasal Administration - Yusuke Hatakawa; Akiko Tanaka; Tomoyuki Furubayashi; Rina Nakamura; Motomi Konishi; Toshifumi Akizawa; Toshiyasu Sakane (MDPI AG, 2021)
We have recently reported Catalytides (Catalytic peptides) JAL-TA9 (YKGSGFRMI) and ANA-TA9 (SKGQAYRMI), which are the first Catalytides found to cleave Aβ42. Although the Catalytides must be delivered to the brain parenchyma to treat Alzheimer's disease, the blood-brain barrier (BBB) limits their entry into the brain from the systemic circulation. To avoid the BBB, the direct route from the nasal cavity to the brain was used in this study. The animal studies using rats and mice clarified that the plasma clearance of ANA-TA9 was more rapid than in vitro degradation in the plasma, whole blood, and the cerebrospinal fluid (CSF). The brain concentrations of ANA-TA9 were higher after nasal administration than those after intraperitoneal administration, despite a much lower plasma concentration after nasal administration, suggesting the direct delivery of ANA-TA9 to the brain from the nasal cavity. Similar findings were observed for its transport to CSF after nasal and intravenous administration. The concentration of ANA-TA9 in the olfactory bulb reached the peak at 5 min, whereas those in the frontal and occipital brains was 30 min, suggesting the sequential backward translocation of ANA-TA9 in the brain. In conclusion, ANA-TA9 was efficiently delivered to the brain by nasal application, as compared to other routes.